School education, dynamics of character's formation and the process of forming personal values - da Silva, Célia Regina; Rosa, Júlia Mazinini [UNESP] (Universidade Federal do Paraná, 2021)
This paper aims to unveil the determinations that make school education one of the human activities which are responsible for creating the formation of values and dynamics that guide the attitudes of individuals. We started by establishing relationships between society, school education, and the formation of individuals. Then we present general characteristics of the character formation's dynamics according to historical-cultural psychology - explained as a product of the concrete activity of individuals - to expose some determinants that fall on the formulation of the guiding values of individual conduct. In this process, we seek to make evident the inevitable impact of school education on the formation of student's conduct. We conclude with the analysis of concrete situations observed in a field study on an early childhood school and extracted from the doctoral thesis of one of the authors (Silva, 2017). We present, then, some perspectives to corroborate intentionally and systematized educational practices towards the transmission of positive valuation related to universal collective interests as a condition for effective individual development.
A educação escolar, dinâmica de formação do caráter e a concretização do processo de formação dos valores pessoais
Keywords: Personal Formation; School Education; Values